Study of Bovine Serum Albumin Solubility in Aqueous Solutions by Intrinsic Viscosity Measurements - Masuelli, Martin Alberto (2013)
The behavior of bovine serum albumin (BSA) in water is scarcely studied, and the thermodynamic properties arising from the experimental measurements have not been reported. Intrinsic viscosity measurements are very useful in assessing the interaction between the solute and solvent. This work discussed in a simple determination of the enthalpy of BSA in aqueous solution when the concentration ranges from 0.2 to 36.71% wt. and the temperature from 35 to 40ºC. The relationship between the concentration and intrinsic viscosity is determined according to the method of Huggins. The temperature increase reduces the ratio between inherent viscosity and concentration (/). This is reflected in the Van't Hoff curve. Furthermore, this work proposes hydrodynamic cohesion value as an indicator of the degree of affinity of protein with water and thermodynamic implications in conformational changes.